The nature of library automation marketplace among academic libraries in Metro Manila - Laceda, Adora Delle A.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
This study was a survey of the library automation marketplace among academic libraries in Metro Manila. The purpose of this study was to determine the status of library automation marketplace among academic libraries in Metro Manila, specifically to identify the software packages used; and to establish trends in library automation among them.
The specific objectives of the study were: 1) to find out the different library software packages used in academic libraries in Metro Manila; 2) to determine who are the major key players in the library automation marketplace; 3) to determine the trends in library automation in Metro Manila; 4) to determine the criteria used for selecting library software; and 5) to determine the features of the different library software packages.
The respondents of this study were chief librarians, library staff and information technology staff. Seventy academic libraries in Metro Manila who are members of the Philippine Association of Academic and Research Libraries (PAARL) were surveyed. Out of the seventy academic libraries, sixty-four (91.4 percent) returned the questionnaire. Among the sixty-four respondents, thirty-seven (57.8 percent) academic libraries are automated while twenty-seven (42.1 percent) are not.
Based on the study, the trend at present is to automate libraries. Most of the software packages used or planned to be used are integrated. They provide different modules and features for a more effective and efficient library service. The three major key players are Info-ed Marketing, who is the local distributor of Sagebrush Corporation (Athena); UNESCO, through the University of the Philippines Institute of Library Science, (CDS/ISIS); and Design Bytes (Maelisa). Cost of the library software, technical considerations and compatibility with the operating system and hardware available in the library, and ease of use are the usual criteria used by academic librarians in selecting software packages.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Computer software; Libraries -- Automation; Academic libraries -- Philippines -- Manila Metropolitan Area